Labour productivity, its main indicators, forms of manifestation, and ways to improve - I. D. Matskulyak (Вестник университета)
The purposes of the article are to study the content of labour productivity, generalise its main indicators, essence of constant trends manifested in the form of an economic law, disclose its forms of manifestation and ways to increase as well as to attract the attention of subjects of these processes to take regulatory measures. The object of the study is labour in the main link of the economy. The subject are political and economic, social and labour relations between participants of the production process regarding the increase in the labour productivity. Its methodological framework covers provisions explaining the nature of the continuity of labour processes based on the labour productivity. Its main sources are considered using the methods of scientific abstraction, comparison, logical, historical, causal, dialectical methods. Among the scientific results is the conclusion about the essence of the economic law of increasing productivity of social labour, about some properties of the forms of its manifestation, number of directions for accelerating the increase and continuity of the labour process. The scientific and practical significance of the article lies in the possible usefulness for the main link of the economy which corrects its own strategies and development programmes of authorities at various levels during the implementation of economic policy as well as of higher educational institutions of the country where economic theory and labour economics are taught.